2013
DOI: 10.1155/2013/796891
|View full text |Cite|
|
Sign up to set email alerts
|

Site-Specific Antioxidative Therapy for Prevention of Atherosclerosis and Cardiovascular Disease

Abstract: Oxidative stress has been implicated in pathophysiology of aging and age-associated disease. Antioxidative medicine has become a practice for prevention of atherosclerosis. However, limited success in preventing cardiovascular disease (CVD) in individuals with atherosclerosis using general antioxidants has prompted us to develop a novel antioxidative strategy to prevent atherosclerosis. Reducing visceral adipose tissue by calorie restriction (CR) and regular endurance exercise represents a causative therapy fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 141 publications
0
15
0
Order By: Relevance
“…It is believed to be a useful measure of antioxidant protection against oxidative damage of membranes and other cellular components [ 58 ]. On the other hand, limited success of preventive cardiology with the use of general antioxidants will probably stimulate future research towards more site-specific antioxidative therapy [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed to be a useful measure of antioxidant protection against oxidative damage of membranes and other cellular components [ 58 ]. On the other hand, limited success of preventive cardiology with the use of general antioxidants will probably stimulate future research towards more site-specific antioxidative therapy [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that higher antioxidant potential can protect the organism against undesirable reactive oxygen species activity and thus prevent disease incidence [ 1 , 2 ]. However, the results of available data are full of discrepancies and the present state of knowledge on such dependence is still not complete [ 6 , 7 ]. It is not evidenced whether the incidence of coronary heart disease (CHD) is related to a decrease in antioxidant potential.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with SLE, increased levels of very LDL cholesterol, triglycerides, and homocysteine and also decreased levels of apoA‐1 and HDL cholesterol have been described . Accordingly, atherosclerosis patients should take preventive therapy based on instructions for blood pressure control, regular exercise, and when the usage of folic acid and statins is necessary . Immunomodulation of atherosclerosis is an interesting option, although it is still in the infancy stage .…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…65,66 Accordingly, atherosclerosis patients should take preventive therapy based on instructions for blood pressure control, regular exercise, and when the usage of folic acid and statins is necessary. 67 Immunomodulation of atherosclerosis is an interesting option, although it is still in the infancy stage. 68 Immunomodulation approaches have been developed based on several methods, including immunosuppression, use of intravenous immunoglobulins (IVIg), induction of oral tolerance with autoantigens (for instance oxLDL), cytokine inhibitors, gene therapy and bone-marrow transplantation.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Astaxanthin does not exert a prooxidant effect typical of other carotenoids [ 57 ]. Furthermore, astaxanthin is not a vitamin precursor hence it's overdose does not pose the threat of hypervitaminosis.…”
Section: Astaxanthinmentioning
confidence: 99%